Dislocation induced twin growth and formation of basal stacking faults in 101¯2 twins in pure Mg. (15th February 2019) - Wang, Fulin; Barrett, Christopher D.; McCabe, Rodney J.; El Kadiri, Haitham; Capolungo, Laurent; Agnew, Sean R.
Abstract: In situ tension experiments were performed on oriented pure Mg single crystal specimens, within a transmission electron microscope. Several microstructure evolutions directly related to the interaction between basal dislocations and 10 1 ¯ 2 tension twin boundary (TB) were observed: (1) dislocation slip-induced twin growth, (2) formation of I 1 stacking faults in the wake of the advancing TB, and (3) development of large interfacial serrations. The associated defects in the twin crystal and on the TB are characterized and quantified, leading to the verification and further elucidation of a dislocation transmutation reaction proposed five decades ago. Aided by molecular dynamics simulations, it is concluded that the slip-twin interaction is not a slip transfer process. When the TB advances, the unit process is the transformation of each basal dislocation to a sessile partial dislocation inside the twin crystal, trailing a I 1 SF. The glissile-to-sessile transition is therefore analogous to the Basinski mechanism. Twinning disconnections (TDs) are generated as a by-product of the dislocation transformation at the TB. Driven by the stress field of basal dislocations in the matrix, the TDs glide on the TB, which firstly produces TB migration and secondly dissipates the strain energy of the incident dislocations. The pile-up of the locally generated TD was observed to induce the formation of severe interfacial serrations, which do not stop TB migration. Graphical abstract: Image 1